Magnetic field enhancement of electrochemical hydrogen evolution reaction probed by magneto-optics. (19th January 2021) - Sambalova, Olga; Billeter, Emanuel; Yildirim, Oguz; Sterzi, Andrea; Bleiner, Davide; Borgschulte, Andreas
Abstract: External magnetic fields affect various electrochemical processes and can be used to enhance the efficiency of the electrochemical water splitting reaction. However, the driving forces behind this effect are poorly understood due to the analytical challenges of the available interface-sensitive techniques. Here, we present a set-up based on magneto- and electro-optical probing, which allows to juxtapose the magnetic properties of the electrode with the electrochemical current densities in situ at various applied potentials and magnetic fields. On the example of an archetypal hydrogen evolution catalyst, Pt (in a form of Co/Pt superlattice), we provide evidence that a magnetic field acts on the electrochemical double layer affecting the local concentration gradient of hydroxide ions, which simultaneously affects the magneto-optical and magnetocurrent response. Highlights: Magnetic field effects on hydrogen evolution probed by in situ magneto-optics. External magnetic fields enhance electrochemical hydrogen evolution on Pt. The effect is linked to the magnetic changes of the electrochemical double layer.